An Analysis of Code-Mixing Used by Livy Renata and Gabriel Prince in A Vlog Video on Livy Renata’s YouTube - Gelgel, Dadi Triana Putri (Jurnal Penelitian Mahasiswa Indonesia, 2023)
The development of various information technologies makes code-mixing now easier to find because information technology such as YouTube allows one to share various types of desired content and find shows that match the audience's wishes. This study discusses the level of code-mixing on Livy Renata's YouTube Channel. This study aimed to find the level of code-mixing of the utterances spoken by Livy Renata and Gabriel Prince. The data analyzed comes from Livy Renata's YouTube video, which was uploaded in June 2022. This data is analyzed using the theory of Suwito (1983), which classifies code-mixing levels into six categories: word level, Phrase Level, Baster Level, Reduplication or repetition, Idiom Level, and Clause level. This study shows that the utterances conveyed by Livy Renata and Gabriel Prince can be classified into Word Level, Phrase Level, Baster Level, and Clause Level, while no data states the utterances are classified as Reduplication or Repetition Level and Idiom Level.